Reduction Of Oil Adsorption In Banana Fritter Balls: The Effect Of Hydrocolloid Substitution - Anuar, Fatin Nabila (Universiti Sains Malaysia, 2020)
The physicochemical properties of banana fritter balls and frying oil quality with substitution of hydrocolloids namely, modified corn starch, carboxylmethyl cellulose (CMC) and gellan gum, in wheat flour were studied. Batter of 100% wheat flour is used as the control samples. Hydrocolloids substitution in wheat flour were prepared by dry mixing of both ingredients at the proportion of 4%, 6%, 8%, 10% and 12%. The batter was prepared by mixing proportion of hydrocolloids with wheat flour, banana, sugar, salt and later fried in heated frying oil at 180°C for 4-5min. Later, the fried samples were analysed for oil content, oil uptake ratio, texture and free fatty acids. The oil content of banana fritter balls decreased significantly with increasing the proportion of hydrocolloids. Proportion of 12% CMC showed the lowest oil content. However, there are no significant difference between 12% modified corn starch, CMC and gellan gum on oil uptake. The oil uptake ratio decreased with increasing the proportions of hydrocolloids. Proportion of 12% CMC showed the lowest oil uptake ratio. However, there are no significant difference between 12% modified corn starch, CMC and gellan gum on oil uptake ratio. For textural analysis banana fritter balls of 12% CMC showed the highest hardness, while 12% of gellan gum showed the highest springiness. On the other hand, 12% gellan gum showed the highest cohesiveness and control samples showed the highest chewiness. Free fatty acids analysis of frying oil was conducted to determine the oil quality. The free fatty acids of frying oil to fry banana fritter balls of 12 % CMC showed the lowest free fatty acids. Overall, the study concluded that substitution of hydrocolloids improves the physicochemical properties of banana fritter balls compared to banana fritter balls made of 100% of wheat flour.